Therapeutic Effects of Persea americana L. Phytochemicals on Key Molecular Targets in Knee Osteoarthritis: An In-silico and In-vivo approach (Nigerian Journal of Physiological Sciences, 2025)
Knee osteoarthritis (KOA) is a prevalent degenerative joint disorder characterized by chronic inflammation, cartilage degradation, and altered bone remodelling. This study investigated the inhibitory effects of Persea americana L. phytochemicals on key molecular targets involved in KOA pathogenesis and compared them with clinically used drugs targeting these pathways. Specifically, Interleukin receptor-associated kinase 4 (IRAK4), Transforming Growth Factor-Beta (TGF-β), Microsomal Prostaglandin E Synthase 1 (mPGES1), Kelch-like ECH-Associated Protein 1 (Keap1), Carbonic Anhydrase 1 (CA1), and Collagen II. Molecular docking analyses were performed using Schrodinger (Maestro 12.12). All proteins' 3D X-ray crystallographic structures were screened based on the following properties (Organism, Expression system, and Resolution) using Protein Data Bank (RCSB PDB) https://www.rcsb.org/. Various lead compounds with significant binding affinities to these targets have been identified, outperforming conventional pharmacological agents. In vivo assessments using the hot plate test were conducted on 30 male Wistar rats, which were divided into six experimental groups. Chemical induction of KOA was performed by intra-articular injection of 25uL of saline dissolved 4 mg/kg of Sodium monoiodoacetate (MIA) in four of five groups: Control, Sham, and 3 treated with Ibuprofen, Low, and High Persea americana L. extracts, respectively, except the KOA only group. The docking scores from all the pathways showed higher binding energy when compared to the present drug samples, except for KEAP 1, where Chlorhexidine "STD" and Quercetin had binding scores of -6.576 and -6.557, respectively. Persea americana L. extracts treated rats showed significantly enhanced pain thresholds in KOA models compared to pathological untreated and ibuprofen-treated groups (p